Concentración mínima inhibitoria de nanopartículas de óxido de zinc sobre el crecimiento de Klebsiella pneumoniae ATCC 700603 - ARIAS LÓPEZ, Pamela María de Fátima (2019)
Zinc oxide nanoparticles represent an alternative to implement efficient measures to inhibit the growth of various microorganisms, especially bacteria like Klebsiella pneumoniae. The present investigation aims to determine the minimum inhibitory concentration of zinc oxide nanoparticles on the growth of Klebsiella pneumoniae ATCC 700603 producer of extended spectrum beta-lactamases (ESBL+). For this, zinc oxide nanoparticles were synthesized and provided by the Multidisciplinary Research Laboratory of UPAO. Then, the strain of Klebsiella pneumoniae ATCC 700603 was reactivated and its average logarithmic phase and generation time were determined. To determine the Minimum Inhibitory Concentration (MIC), the technique of macrodilution in broth was used in 10 experimental sterile tubes with Müller Hinton broth at different concentrations of ZnO nanoparticles, to which a suspension of the bacteria in its average logarithmic phase standardized to tube N° 0,5 of McFarland was added. Three repetitions of the process were done and it was obtained as a result a MIC of 0.5 mg/mL. Therefore, zinc oxide nanoparticles have the ability to inhibit the growth of Klebsiella pneumoniae ATCC 700603.